Beyond the Gender Divide: Looking for Shakespeare in Han Tae-Sook's Lady Macbeth. (7th January 2016) - Im, Yeeyon
Abstract : Han Tae-Sook's Lady Macbeth, a theatre adaptation by a leading woman director in Korea, has been interpreted largely from a feminist and intercultural perspective. In this article Yeeyon Im examines a body of criticism on Han's production to raise awareness of the danger of totalization in current critical geography in Korea, which may marginalize non-ideological views. The humanist issues of evil, desire, and guilt, which are explicit themes of Lady Macbeth, have been neglected by critics in favour of discourses of difference. Yeeyon Im asks if 'the subaltern can speak' of universality, and calls for a new literary humanism that allows reflection on how to live through the help of literature. Yeeyon Im is Associate Professor of English at Yeungnam University in South Korea, where she teaches Shakespeare and drama. She has published widely on Shakespeare and modern drama. Her articles on intercultural Shakespeare productions of Lee Yountaek and Ninagawa Yukio have appeared in Theatre Journal, Shakespeare, and Shakespeare Bulletin . She has also translated into Korean plays by Ben Jonson ( Volpone and The Alchemist ) and Christopher Marlowe ( Dido, Queen of Carthage ).